Respon Terhadap Konflik Oleh Masyarakat Komunitas Kontu dalam Kawasan Hutan Lindung Jompi Kabupaten Muna Sulawesi Tenggara - Laode Muhammad Iqbal; Muhammad Dasir; Risma Illa Maulany (Jurnal Hutan dan Masyarakat, 2019)
The case of conflict occurring in the Jompi protected forest is a conflict between the Kontu community and the Muna District Forest Service. The problems that occur because the community is not allowed to enter the protected forest area while the people from the past have lived and has dependent in the forest. The community's productive land is within Jompi's protected forest area. History notes that the protected forest area of Jompi has been traditionally utilized by the community of Kontu communities. So that social pressure of the community then manages the land in the Forest area without permission from the Forest Service. This is done by Kontu and the poor from the city of Raha to make ends meet. Based on this case, this study examines how the responses about the conflicts by Kontu communities in utilizing the Jompi protected forest area, Muna Regency, Southeast Sulawesi. Data analysis is done descriptively narrative which presents data descriptively in the form of chart, matrix to facilitate comprehension of data analysis result which have obtained more integrated. The results obtained in this study that the causes of the conflict that occurred between Kontu Community and Muna District Forest Service began in 1999, when the issuance of Forestry Ministerial Decree No. 454 / Kpts-II / 1999 by the Ministry of Forestry which designates the forest area of Southeast Sulawesi. Communities respond to conflict in different ways. Some communities respond strongly that those expressed in the form of resistance as their resistance to conflict and there is also a weak response, expressed by migration although not so much.